On Bubble-Particle Detachment Mechanisms in Coarse Particle Flotation - S. Mitra1 (International Mineral Processing Congress, 2018)
"This study aims to investigate coarse particle detachment mechanisms (particle diameter > 150 ?m) utilising both experimental and numerical technique. Two mechanisms were studied – (i) interactions of bubbleparticle (BP) aggregate with vortices and (ii) coalescence of bubble-particle aggregates. On the first mechanism, interaction behaviour of coherent vortex structures with a BP aggregate (bubble diameter db = 3 mm, particle diameter dp = 0.3 mm) was studied using a CFD model in the Reynolds number range of 100 to 1000. Effect of surface hydrophobicity on the BP stability was examined using a range of contact angle boundary conditions. To address the second mechanism, interactions of bubble-particle aggregate (db ~ 4 mm, dp ~ 0.4 mm) with both free gas-liquid interface and individual bubbles were investigated using high speed imaging. Both rebound and coalescence outcomes were observed to be responsible for BP instability leading to particle detachment.INTRODUCTIONIt is widely known that flotation process performs excellent mineral recovery for base metal ore particles that are typically in the range of ~ 20 to 150 µm in diameter (Jameson, 2010). More specifically, higher recoveries are usually reported for particles in the size range of ~20 to 70 µm while outside this spectrum, generally the recovery diminishes significantly. It would be highly desirable to improve the recovery of particles at the coarse end of the flotation size range spectrum which has significant economic benefit (Jameson, 2010). However, it is essential that insights to particle detachment phenomenon, the primary impediment in coarse particle flotation caused by the underlying hydrodynamic factors are first obtained at a greater depth.In an ideal quiescent liquid medium, due to inertia, coarse particles deviate substantially from the fluid streamlines and collision efficiency with bubbles decreases which can only be augmented by increasing turbulence level in the medium sufficiently to make random physical contacts with bubbles. Nonetheless, even if successful contacts are made, it is difficult for these large particles to remain attached to bubbles in a turbulent shear flow environment. There are two major mechanisms postulated for particle detachment – interaction of turbulent flow structures (eddies) with BP aggregate and coalescence among surrounding aggregates. Earlier work of Schulze (1982) theorised a vortex acceleration component to characterise turbulence effect on BP aggregate instability in flotation machines. Wang et al. (2015) investigated bubble detachment behaviour from a stationary particle in a nearly homogeneous and isotropic flow field. Using PIV (particle image velocimetry), it was shown that the local maximum energy dissipation rate for the case of bubble detachment was significantly higher than the no detachment case, and was also higher than the critical value for bubble detachment calculated using Schulze’ theory (Schulze, 1982). Later, Wang et al. (2017) also visualised the BP aggregate instability in a cavity flow leading to particle detachment which was attributed to bubble coalescence, bubble surface oscillation and particle deceleration phenomena."